Omeprazole limited sampling strategies to predict area under the concentration-time curve ratios: implications for cytochrome P450 2C19 and 3A phenotyping. - Lawson, Eileen; Wu, Jerry; Baldwin, R.; Ingelman-Sundberg, Magnus; Rosenborg, Staffan; Yim, Dong-Seok; Yin, Ophelia; Capparelli, Edmund; Ma, Joseph (European Journal of Clinical Pharmacology, 2012)
Purpose: To develop a limited sampling strategy (LSS) to predict area under the concentration-time curve (AUC) ratios of omeprazole (AUC) to its metabolites 5-hydroxyomeprazole (AUC) and omeprazole sulfone (AUC) as phenotyping parameters for cytochrome P450 (CYP) 2C19 and 3A. Methods: Data were obtained from 37 (4 women) Caucasian, Chinese, and Korean healthy adults from three published studies. The AUC, AUC, and AUC were calculated via noncompartmental analysis. Observed AUC/AUC and AUC/AUC were determined. Plasma concentrations of omeprazole, 5-hydroxyomeprazole, and omeprazole sulfone at 1, 1.5, 2, 3, 4, 6, and 8 h post-dose were used to generate limited sampling strategy (LSS) models to predict AUC/AUC and AUCAUC. Bias and precision were assessed via percentage mean prediction error (%MPE) and percentage mean absolute error (%MAE), with acceptable limits being <15%. Results: For CYP2C19, the AUC/AUC was [mean ± standard deviation (SD)] 2.10 ± 1.63. Five LSS models of AUC/AUC were generated, but none met the bias or precision criteria. Upon stratification by CYP2C19 genotype and ethnicity, a three-timepoint (at 1, 2, and 4 h) LSS model accurately predicted AUC/AUC in Caucasian CYP2C19*1/*1 subjects. For CYP3A, AUC/AUC (mean ± SD) was 1.79 ± 0.67. All LSS models had unacceptable %MAE, even when stratified by CYP2C19 genotype and ethnicity. Conclusions: A LSS model to predict AUC/AUC, and thus CYP2C19 activity, was generated for Caucasian CYP2C19*1/*1 subjects. However, additional model validation is needed prior to general use. LSS models to predict AUC/AUC, and thus CYP3A activity, were not possible, even upon stratification by CYP2C19 genotype and ethnicity.